Quality evaluation and determination of heavy metal contents in palm oil - Khan, MSH; Sikdar, KMYK; Saqueeb, N; Hossain, MH; Ahmed, F; Faroque, ABM; Sarkar, MR (Bangladesh Journal of Scientific and Industrial Research, 2020)
Palm oil is an edible vegetable oil, extracted from the fruit of the Elaeis guineensis which is used for frying foods in most of the restaurants and confectionaries as well as for cosmetic preparations in industries. As the quality of palm oil in Bangladesh is deteriorating day by day, ten brands (S-1 to S-10) of commercially available palm oils were collected from different local markets, their physicochemical properties were tested and compared with the standard parameters stated by Bangladesh Standards and Testing Institution (BSTI). Results revealed that the acid value, free fatty acid value and relative density of all the palm oils (S-1 to S-10) were within the range of BSTI standard. However, the saponification value, peroxide value, iodine value, insoluble impurities and moisture content were much higher than the ranges of BSTI standard in all the samples. Moreover, lead content was higher than the standard value (>0.1 ppm) in brands S-1, S-4 and S-10. In addition, Copper and Iron contents were higher than the BSTI standards (0.1 and 1.5 ppm) in all the tested samples, whereas Cadmium content was below than the standard level (1.0 ppm). Bangladesh J. Sci. Ind. Res.55(4), 301-310, 2020